Study to assess knowledge, attitude and practice regarding organ donation among interns of a medical college in Telangana, India - Jothula, Kishore Y.; D., Sreeharshika (International Journal Of Community Medicine And Public Health, 2018)
Background: There is a gradual decrease in health status and daily functioning in patients with end stage organ failure and timing of death remains uncertain. Organ transplantation is the only cure to such patients. Organ donation rate in India is only 0.26 per million. This is due to lack of awareness about the need of organ donation and the ignorance of common men and medical fraternity about the importance, procedures, benefits and legal issues of organ donation. The objective of this study is to assess the knowledge, attitude and practice regarding organ donation among medical interns. Methods: A cross-sectional study was conducted among 160 interns with a pre-tested, semi structured questionnaire in order to assess their knowledge, attitude and practice regarding organ donation. Data collected was analysed using SPSS software. Results: The mean age of the interns was 23.03±0.73 and majority were females (70%). 79.4% of interns were having adequate knowledge and majority (77.5%) were willing for organ donation. Only 5.6% had donor card. Willingness for organ donation was significantly associated with knowledge about organ donation. The major barrier for organ donation was fear of organs misuse. Most common source of information was found to be internet. Conclusions: Though most of the interns had adequate knowledge, still gaps exist in their knowledge, attitude and practices. By giving right knowledge and orientation medicos can be become future organ donors who can then easily motivate their patients to follow the path.